Peran Bumdes dalam Pembangunan Pariwisata Berkualitas dan Berkelanjutan di Lereng Sumbing, Desa Temanggung, Kecamatan Kaliangkrik, Kabupaten Magelang - Muhamad Muhamad; Sri Rahayu Budiani; Nurul Chamidah; Endah Nurhawaeny Kardiyati; Mardiyanto Adjie (Penerbit Goodwood, 2022)
Purpose: The most important objective in this study is to understand the role of Village-owned Enterprises (BUMDes) in strengthening innovations developed by rural communities. The presence of BUMDes is the right of the village in giving authority to the village government to innovate in village development, especially in terms of improving the village economy and welfare for rural communities in the development of quality and sustainable tourism. Method: The study method developed is qualitative descriptive research method that utilizes qualitative data which is often used to analyze events, phenomena, or social conditions. Results: The results of the study show that the support of Bumdes plays a role in increasing sustainable tourism development, one of which is in the form of preparing documents for assisting sustainable tourism development. One of the supports from BUMDes takes form as efforts to collaborate with elements of universities and local governments as well as Corporate Social Responsibility (CSR). Limitation: The limited time for the implementation of the service is very short, namely 6 months. Contribution: Contribution enterprises (BUMDes) in strengthening innovations developed by rural communities.